Effectiveness of MRI in Detecting and Diagnosing Brain Tumors in Children: A Meta-Analysis - Hidayat, Rachmat (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Brain tumors are one of the most common types of cancer in children. Accurate and timely diagnosis is essential to determine optimal treatment and improve patient prognosis. Magnetic resonance imaging (MRI) has become one of the main imaging modalities for detecting and diagnosing brain tumors in children. Methods: A meta-analysis was conducted to evaluate the effectiveness of MRI in detecting and diagnosing brain tumors in children. Twelve studies that met the inclusion criteria were evaluated for sensitivity, specificity, positive predictive value (NPV), negative predictive value (NPV), and positive likelihood ratio (LR+). Results: The results of the meta-analysis showed that MRI had a sensitivity of 92.5% (95% CI: 86.4% - 96.7%) and a specificity of 97.3% (95% CI: 94.2% - 99.0%) for detecting brain tumors in children. NPV and LRP+ were 97.0% (95% CI: 93.8% - 99.2%) and 33.1 (95% CI: 11.8 - 117.2), respectively. Conclusion: MRI is recommended as the imaging modality of choice for detecting and diagnosing brain tumors in children.